Bioefficacy evaluation of liquid inoculants and antagonisticActivity of rhizobia against fungal pathogens - V. NITHYAKALYANI; M. KANNAN (International Journal of Pharma and Bio Sciences, 2017)
Rhizobia are a unique class of prokaryotes which can improve growth and yield of legumes by developing a symbiotic relationship. This interaction reduces the need of nitrogenous fertilizers during the growth of leguminous crop. So rhizobial inoculants have been frequently applied as biofertilizers having antagonistic activity against various soil-borne plant pathogenic fungi. In this study Rhizobium strain was evaluated for antagonistic activity against fungal pathogens, shelf life studies of liquid formulants using biopolymers and pot trials along with control were performed. Isolated Rhizobium inhibited the growth of Aspergillus niger and Fusarium oxysporum which are pathogenic fungi affecting yield of groundnut plants. The isolate was characterized for its physiological stability in different polymers. The obtained strain showed higher viability throughout the shelf life period in all polymers such as carboxy methyl cellulose (CMC), poly ethylene glycol (PEG), poly vinyl pyrolidone (PVP) and sodium alginate (SA) at various concentrations during 9 months (7days to 180 days). Groundnut seeds treated with liquid bioinoculants showed significant influence on the physical parameters of plants as compared with control under pot experiment trials.All the parameters of growth of groundnut plant showed good results for rhizobium inoculation of seeds. Therefore such isolates may be beneficial strains to improve growth and development of groundnut plants.